Distinct forms of synaptic inhibition and neuromodulation regulate calretinin-positive neuron excitability in the spinal cord dorsal horn. (21st June 2016) - Smith, K.M.; Boyle, K.A.; Mustapa, M.; Jobling, P.; Callister, R.J.; Hughes, D.I.; Graham, B.A.
Graphical abstract: Highlights: CR+ spinal dorsal horn neurons form excitatory (Typical) and inhibitory (Atypical) subpopulations. Typical neurons received mixed (GABAergic and glycinergic) inhibition. Atypical neurons received inhibition dominated by glycine. Noradrenaline and serotonin evoke responses in Typical but not Atypical neurons. Enkephalins evoke responses in Atypical but not typical neurons. Abstract: The dorsal horn (DH) of the spinal cord contains a heterogenous population of neurons that process incoming sensory signals before information ascends to the brain. We have recently characterized calretinin-expressing (CR+) neurons in the DH and shown that they can be divided into excitatory and inhibitory subpopulations. The excitatory population receives high-frequency excitatory synaptic input and expresses delayed firing action potential discharge, whereas the inhibitory population receives weak excitatory drive and exhibits tonic or initial bursting discharge. Here, we characterize inhibitory synaptic input and neuromodulation in the two CR+ populations, in order to determine how each is regulated. We show that excitatory CR+ neurons receive mixed inhibition from GABAergic and glycinergic sources, whereas inhibitory CR+ neurons receive inhibition, which is dominated by glycine. Noradrenaline and serotonin produced robust outward currents in excitatory CR+ neurons, predicting an inhibitory action on these neurons, but neither neuromodulator produced a response in CR+ inhibitory neurons. In contrast, enkephalin (along with selective mu and delta opioid receptor agonists) produced outward currents in inhibitory CR+ neurons, consistent with an inhibitory action but did not affect the excitatory CR+ population. Our findings show that the pharmacology of inhibitory inputs and neuromodulator actions on CR+ cells, along with their excitatory inputs can define these two subpopulations further, and this could be exploited to modulate discrete aspects of sensory processing selectively in the DH.